The Influence of Social Media and the Surrounding Natural Environment as Learning Resources on the Formation of Student Discipline Character - Kasmin, Muhamad; Yunus, Muh.; Syarifuddin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze: 1) the effect of social media on the development of students' discipline character at SD Kecil Mario, Tondong Tallasa District, 2) the influence of the surrounding natural environment on the formation of students' discipline character, 3) the simultaneous effect of social media and the surrounding natural environment on students' discipline character, and 4) the dominant variable affecting the formation of students' discipline character. Using a quantitative approach, data were collected through a questionnaire from 86 students using a saturated sampling technique. Data were analyzed using multiple regression, t-test, and F-test with SPSS 26. The results show that both social media and the natural environment significantly influence students' discipline character, with the natural environment.